Azole-Resistant Aspergillus fumigatus Among Danish Cystic Fibrosis Patients: Increasing Prevalence and Dominance of TR34/L98H - Risum, Malene; Hare, Rasmus Krøger; Gertsen, Jan Berg; Kristensen, Lise; Johansen, Helle Krogh; Helweg-Larsen, Jannik; Abou-Chakra, Nissrine; Pressler, Tacjana; Skov, Marianne; Jensen-Fangel, Søren; Arendrup, Maiken Cavling (Frontiers in Microbiology, 2020)
Azole resistant (azole-R) Aspergillus is an increasing challenge worldwide. Patients with cystic fibrosis (CF) are at risk of Aspergillus colonisation and disease due to a favourable lung environment for microorganisms. We performed a nationwide study in 2018 of azole-non-susceptible Aspergillus in CF-patients and compared with data from two prior studies. All airway samples with mould isolates from patients monitored at the two CF-centres in Denmark (RH, Jan-Sept and AUH, Jan-Jun) were included. Classical species identification (morphology and thermo-tolerance) was performed and MALDI-TOF/β-tubulin sequencing if needed. Susceptibility was determined using EUCAST E.Def 10.1 and E.Def 9.3.2. cyp51A sequencing and STRAf genotyping were performed for azole-non-susceptible isolates and relevant sequential isolates. In total, 340 mould isolates from 159 CF-patients were obtained. The most frequent species were Aspergillus fumigatus (266/340, 78.2%) and Aspergillus terreus (26/340, 7.6%). Azole-R A. fumigatus was cultured from 7.3% (10/137) patients, including 9.5% (9/95) patients at RH and 2.4% at AUH (1/42), respectively. In a 10-year perspective, azole-non-susceptibility increased numerically among patients at RH (10.5% in 2018 versus 4.5% in 2007-2009). Cyp51A resistance mechanisms were found in nine azole-R A. fumigatus from eight CF-patients. Five were of environmental origin (TR34/L98H), three were human medicine driven (two M220K and one M220R) and one was novel (TR343/L98H) and found in a patient who also harboured a TR34/L98H isolate. STRAf genotyping identified 27 unique genotypes among 45 isolates and ≥2 genotypes in 8/12 patients. This included one patient carrying two unique TR34/L98H isolates, a rare phenomenon. Genotyping of sequential TR343/L98H and TR34/L98H isolates from the same patient showed only minor differences in 1/9 markers. Finally, Azole-R A. terreus was found in three patients including two with Cyp51A alterations (M217I and G51A, respectively). Azole-R A. fumigatus is increasing among CF-patients in Denmark with the environmentally associated resistance TR34/L98H mechanism being dominant. Mixed infections (wildtype/non-wildtype and several non-wildtypes) and a case of potential additional tandem repeat acquisition in vivo were found. However, similar genotypes were identified from another patient (and outside this study), potentially suggesting a predominant TR34/L98H clone in DK. These findings suggest increasing prevalence and complexity of azole resistance in A. fumigatus.